Relationships between physical-geographical factors and soil degradation on agricultural land - Bednář, Marek; Šarapatka, Bořivoj (Environmental research. Section A, 2018)
It is a well-known fact that soil degradation is dramatically increasing and currently threatens agricultural soils all around the world. The objective of this study was to reveal the possible connection between soil degradation and seven physical-geographical factors - slope steepness, altitude, elevation differences, rainfall, temperature, soil texture and solar radiation - in the form of threshold values (if these exist), where soil degradation begins and ends. The analysis involved the whole area of the Czech Republic which consists of 13,027 cadasters (78,866 km2). The greatest total degradation threat occurs in areas with slope steepness >7 degrees, average annual temperature <5.9 °C, elevation differences >10.54, altitude >766 m a.s.l. Similarly, the results for water erosion, wind erosion, soil compaction, loss of organic matter, acidification and heavy metal contamination were processed. The results enable us to identify the relationships of different levels of threats which could consequently be used in various ways - for classification of threatened areas, for more effective implementation of anti-degradation measures, or purely for a better understanding of the role of physical geographical factors in soil degradation in the Czech Republic, and thus could increase the chances of reducing vulnerability to land degradation not only in the Czech Republic.
Keywords: zachování přírodních zdrojů; Česká republika; Soil; půda; Geography; Conservation of Natural Resources; Czech Republic; zemědělství; Agriculture; zeměpis